Теорія літературних жанрів у світлі сучасних міждисциплінарних учень: емпіричний та онтологічний дискурси - Драненко, Галина; Dranenko, Galyna (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті досліджено проблему взаємозв’язку категорій жанр / текст у контексті сучасної гуманіта¬рис¬тики. Схарактеризовано принципи міждисциплінарного підходу в осмисленні сутності процесів трансформацій жанрових одиниць та їх генези. Окрему увагу приділено онтологічній концепції розуміння жанрів Ж.-М. Шафера, який трактує жанр як категорію ретроспективної класифікації, а жанровість вивчає як текстуальну функцію. The article deals with the essence of the interdisciplinary empirical and ontological discourses on problem solving of the genre transformations and of the transgressions. Besides, we illustrated the processes of the genre modulations, which favour the development of the new approaches of the studding of the genre forms. We stressed on the contribution of the pragmatic and the reception aesthetics to the denotation of the notion of the genre category and the genre competencies of the reader. A particular attention has been paying to the ontological conception of the modern French philosopher J. M. Schaeffer who defines a genre as a category of retrospective classification, and g?n?ricit? as a textual function. It is investigated the genre functions as a dynamic category since the genre is the reference point of the genre transgression and the waiting horizon of the recipient. Weoutlined the peculiarities of the genre dynamic by means of the concept of the prototypicalensemble. We showed the manner in which the genre prototype composed of the center and the peripherals represent the dominant genre criterion in the certain period.
The Theory of the Literary Genres in the Light of the Modern Interdisciplinary Studies: the Empirical and the Ontological Discourses
Keywords: жанрологія; жанр; текст; жанровість; жанрова категорія; Ж.-М. Шафер; genereology; genre; text; genericite; genre category; Jean-Marie Schaeffer